Hydroxyl Radical vs. One-Electron Oxidation Reactivities in an Alternating GC Double-Stranded Oligonucleotide: A New Type Electron Hole Stabilization - Annalisa Masi; Amedeo Capobianco; Krzysztof Bobrowski; Andrea Peluso; Chryssostomos Chatgilialoglu (Biomolecules, 2023)
We examined the reaction of hydroxyl radicals (HO•) and sulfate radical anions (SO4•−), which is generated by ionizing radiation in aqueous solutions under anoxic conditions, with an alternating GC doubled-stranded oligodeoxynucleotide (ds-ODN), i.e., the palindromic 5′-d(GCGCGC)-3′. In particular, the optical spectra of the intermediate species and associated kinetic data in the range of ns to ms were obtained via pulse radiolysis. Computational studies by means of density functional theory (DFT) for structural and time-dependent DFT for spectroscopic features were performed on 5′-d(GCGC)-3′. Comprehensively, our results suggest the addition of HO• to the G:C pair moiety, affording the [8-HO-G:C]• detectable adduct. The previous reported spectra of one-electron oxidation of a variety of ds-ODN were assigned to [G(-H+):C]• after deprotonation. Regarding 5′-d(GCGCGC)-3′ ds-ODN, the spectrum at 800 ns has a completely different spectral shape and kinetic behavior. By means of calculations, we assigned the species to [G:C/C:G]•+, in which the electron hole is predicted to be delocalized on the two stacked base pairs. This transient species was further hydrated to afford the [8-HO-G:C]• detectable adduct. These remarkable findings suggest that the double-stranded alternating GC sequences allow for a new type of electron hole stabilization via delocalization over the whole sequence or part of it.